Integrating Ecocritical Approach in Poetry Teaching to Enhance Environmental Awareness Among Junior High School Students - Wirawan, Abdul Karim; Abdillah, Khumaidi (Cognitive Insight in Education, 2025)
This research aims to analyze the integration of ecocritical approaches in poetry teaching and their potential in enhancing environmental awareness among junior high school students. This study employs a qualitative approach with a library research methodology that analyzes various primary and secondary sources, including scientific journal articles, reference books, and academic publications, related to literary ecocriticism, poetry pedagogy, and environmental education. The collected data were analyzed using qualitative content analysis techniques with a thematic approach to identify conceptual patterns and build a synthesis of understanding regarding the integration of ecocriticism in poetry learning. The research findings suggest that integrating ecocritical approaches into poetry teaching can be implemented through a systematic process encompassing the selection of ecologically themed poetry, the development of relevant learning contexts, textual exploration from ecocritical perspectives, and the implementation of creative activities. Students' responses to this learning approach demonstrate the complexity of reactions that encompass emotional, cognitive, and social dimensions with high levels of participation. Changes in students' environmental awareness are manifested in multidimensional transformations that include the development of systemic understanding of ecosystems, the strengthening of emotional connections with nature, the evolution of moral orientation from anthropocentric to ecocentric perspectives, and the formation of strong environmental identity. This research recommends the development of literary learning models that integrate ecocritical approaches as an effective strategy to support sustainable environmental education and the formation of an environmentally conscious character from an early age. The study contributes to the advancement of pedagogical frameworks that bridge literary education with environmental consciousness, offering practical implications for curriculum development and instructional design in secondary education contexts.